SOCIALIZATION OF THE BENEFITS OF CAPITAL MARKET STOCK EXCHANGE FOR THE COMMUNITY IN MEUNASAH TUHA ACEH BESAR DISTRIC - Fitri, Aida; Anam, Budi Safatul; Murhadi, Thasrif; Mimiasri, Mimiasri; Wiratama, Muhammad Jaka (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2023)
Objective this community service is foradd knowledge and insight regarding the benefits of the Capital Market Stock Exchange for the people of Meunasah Tuha, Aceh Besar District. The output obtained from this community service activity includes (1) participants, can addknowledge and insight about the benefits of the Capital Market Stock Exchange that can be used in carrying out and developing ways of investing(2) From the results of the socialization, participants understood the contents of the material and at the end of the session were given question and answer time, several questions were obtained from participants and the public including: (a) What is the role of the Stock Exchange for investors (b) How does the capital market work system for investors who are not buying and selling for 1 month (c) what are the functions and benefits of the stock exchange for investors   Keyword : Benefits of the Indonesian Stock ExchangeObjective this community service is foradd knowledge and insight regarding the benefits of the Capital Market Stock Exchange for the people of Meunasah Tuha, Aceh Besar District. The output obtained from this community service activity includes (1) participants, can addknowledge and insight about the benefits of the Capital Market Stock Exchange that can be used in carrying out and developing ways of investing(2) From the results of the socialization, participants understood the contents of the material and at the end of the session were given question and answer time, several questions were obtained from participants and the public including: (a) What is the role of the Stock Exchange for investors (b) How does the capital market work system for investors who are not buying and selling for 1 month (c) what are the functions and benefits of the stock exchange for investors  Keyword : Benefits of the Indonesian Stock Exchange